Antidepressant-like Effects of BDNF and NGF Individual Loop Dipeptide Mimetics Depend on the Signal Transmission Patterns Associated with Trk - Armen G. Mezhlumyan; Anna V. Tallerova; Polina Y. Povarnina; Aleksey V. Tarasiuk; Nellya M. Sazonova; Tatiana A. Gudasheva; Sergey B. Seredenin (MDPI AG, 2022)
Neurotrophins are considered as an attractive target for the development of antidepressants with a novel mechanism of action. Previously, the dimeric dipeptide mimetics of individual loops of nerve growth factor, NGF (GK-6, loop 1; GK-2, loop 4) and brain-derived neurotrophic factor, BDNF (GSB-214, loop 1; GTS-201, loop 2; GSB-106, loop 4) were designed and synthesized. All the mimetics of NGF and BDNF in vitro after a 5-180 min incubation in a HT-22 cell culture were able to phosphorylate the tropomyosin-related kinase A (TrkA) or B (TrkB) receptors, respectively, but had different post-receptor signaling patterns. In the present study, we conduct comparative research of the antidepressant-like activity of these mimetics at acute and subchronic administration in the forced swim test in mice. Only the dipeptide GSB-106 that in vitro activates mitogen-activated protein kinase/extracellular signal-regulated kinase (MAPK/ERK), phosphoinositide 3-kinase/protein kinase B (PI3K/AKT) and phospholipase C-gamma (PLCγ) post-receptor pathways exhibited antidepressant-like activity (0.1 and 1.0 mg/kg, ip) at acute administration. At the same time, the inhibition of any one of these signaling pathways completely prevented the antidepressant-like effects of GSB-106 in the forced swim test. All the NGF mimetics were inactive after a single injection regardless of post-receptor in vitro signaling patterns. All the investigated dipeptides, except GTS-201, not activating PI3K/AKT in vitro unlike the other compounds, were active at subchronic administration. The data obtained demonstrate that the low-molecular weight BDNF mimetic GSB-106 that activates all three main post-receptor TrkB signaling pathways is the most promising for the development as an antidepressant.